THE RESERVES OF FISCAL POLICY TO ENSURE THE ECONOMIC GROWTH OF THE COUNTRY - M. Ibrahim (Вестник университета)
Analysis The impact of reserves fiscal policy on the economy as a result of federal crisis 2014 in modern review here . The challenge role of the state in the economy in mentioned , as well as its presence in all phases of economy crisis. conclusion model. Problem in public sector prevent the economy from boasting. These proposals are not just a revision of the notions of achieving economic growth and deliver new tools for economic growth.